Meningkatkan Minat Baca Pada Anak Melalui Kegiatan Read Aloud Pada Anak Usia 5-6 Tahun - Noviatun Aisah; Wafa Aerin (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to improve the reading interest of children aged 5–6 years through read aloud activities at RA NU Kincang. The research subjects consisted of teacher and 30 children in Group B, including 17 boys and 13 girls. The method used was Classroom Action Research (CAR) conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. Data were collected through observations on three main indicators: children’s attention, willingness to retell or repeat reading, and engagement. The results showed a significant increase in all three indicators. Children’s attention increased from 43% at the initial stage to 95% in the second reflection. The willingness to retell or repeat reading increased from 50% to 98%, while engagement rose from 40% to 95%. Read aloud activities, delivered with engaging intonation, expressive gestures, and warm interaction between teachers and children, created a joyful, interactive learning environment suitable for early childhood. Children became more focused, enthusiastic, and active, while simultaneously fostering curiosity, love for books, language skills, imagination, and self-confidence. This study confirms that reading aloud is an effective strategy for fostering reading interest and supporting early literacy development in young children. In the context of Early Childhood Islamic Education, reading aloud activities have implications as a learning strategy that can integrate literacy development with the instillation of Islamic values, such as learning etiquette, a love of knowledge, and the formation of morals from an early age through meaningful stories